Inside the Black Box: Understanding key drivers of global emission scenarios. (January 2019) - Koomey, Jonathan; Schmidt, Zachary; Hummel, Holmes; Weyant, John
Abstract: Technology and policy implications of global energy and emissions scenarios can be difficult to analyze because underlying assumptions and drivers of scenarios are rarely made explicit. This article documents methods for standardizing emissions scenario results that can be applied to virtually any scenario, enabling more meaningful comparisons among scenarios than has been possible in the past. This approach uses charts showing the dynamics and effects of emission drivers, mitigation technologies, and policies. Applying these methods will enable the policy and research communities to better understand the implications of scenarios, and help analysts learn more rapidly. As a matter of good practice, modelers should create decompositions like the ones put forth in this article, policy makers should request them, and funders of scenario analysis and sponsors of model comparisons should support the application and further development of such tools. Highlights: Global energy and emissions scenario results can be hard to analyze and interpret. Standardized "dashboards" allow accurate & rapid comparisons of scenario results. We develop, document, and present decomposition methods to facilitate such comparisons. These tools should promote greater understanding and faster modeling innovation. Policy makers & sponsors should demand such dashboards from modelers in future.